The Role of Internal Control Systems in Improving the Quality of Financial Reports of Microfinance Institutions - A. Asrah Baeduri; Betty Betty; Rahayu Indriasari; Rahma Masdar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This qualitative case study analyzes the role of internal control systems in improving financial report quality at Microfinance Institution (MFI) Mitra Surya Sejahtera, Pasangkayu Regency, using the COSO framework. Data were collected through in-depth interviews, observation, and documentation from management, finance department, and operational staff, with validity tested through triangulation.Results demonstrate that the internal control system significantly enhances financial report quality in terms of reliability, recording orderliness, and accountability. The control environment, supported by management's commitment to integrity and transparency, encourages employee work discipline. Control activities including transaction authorization, evidence completeness, and routine reconciliation effectively minimize recording errors. Regular financial communication and management monitoring further support the preparation of orderly and accountable reports. However, limitations were identified, including constrained human resources, suboptimal separation of functions, and a simple recording system. The study concludes that strengthening internal control systems is crucial for improving financial report quality and maintaining MFI operational sustainability. Findings contribute theoretically to micro-sector accounting literature and practically provide guidance for MFI managers in establishing transparent and accountable financial governance.